Evaluation of prognostic factors after radical prostatectomy in pT3b prostate cancer patients in Japanese population. (15th May 2015) - Inoue, Takahiro; Kinoshita, Hidefumi; Terada, Naoki; Kobayashi, Takashi; Yamasaki, Toshinari; Matsui, Yoshiyuki; Kamba, Tomomi; Inui, Hidekazu; Sugi, Motohiko; Matsuda, Tadashi; Ogawa, Osamu
Abstract : Objective: The purpose of the current study was to evaluate prognostic factors after radical prostatectomy for prostate cancer patients with seminal vesicle invasion (pT3b) in the Japanese population. Methods: Between January 2005 and December 2011, 814 patients underwent radical prostatectomy without neoadjuvant hormonal therapy at our institutions. Among these patients, 31 were (3.8%) presented with pT3b. Kaplan–Meier method was used to determine biochemical recurrence-free, disease-specific and overall survival of patients in this group. Proportional hazards models were used to determine predictors of biochemical recurrence-free survival. Results: The median follow-up period was 60 months (range, 9–108 months). During follow-up, 23 patients (74.2%) experienced biochemical recurrence, and the overall 3-year probability of freedom from biochemical recurrence was 29%. However, only one patient died of the disease, and the 5-year overall survival was 92%. In multivariate analysis, age at the time of surgery was the only significant variable for predicting biochemical recurrence after radical prostatectomy ( P = 0.0356, hazard ratio = 0.92, 95% confidence interval = 0.851–0.994). Conclusions: Patients with seminal vesicle invasion of pathological specimens after radical prostatectomy have high biochemical recurrence, but the survival was favorable especially in light of current multimodal treatment regimens. However, patients with younger age at the time of surgery, in particular, should receive multimodal treatments to improve their outcome.